Adequate Infliximab Exposure During Induction Predicts Remission in Paediatric Patients With Inflammatory Bowel Disease. Issue 6 (June 2019) - van Hoeve, Karen; Dreesen, Erwin; Hoffman, Ilse; Van Assche, Gert; Ferrante, Marc; Gils, Ann; Vermeire, Séverine
ABSTRACT: Objectives: Therapeutic drug monitoring has been proposed as a useful tool in the management of infliximab (IFX) treated patients with inflammatory bowel disease. The aim of this retrospective study was to determine whether IFX trough levels after induction therapy are predictive for outcome at week 52. Methods: All pediatric patients with inflammatory bowel disease receiving maintenance IFX at our centre, with IFX trough level available at their first maintenance infusion and a follow-up of at least 52 weeks were included. IFX induction regimens could be intensified at the discretion of the treating physician. All children received proactive drug monitoring during maintenance with dose adaptation aiming to target a therapeutic window of 3 to 7 μg/mL. Results: We included 35 children (23 with Crohn disease and 12 with ulcerative colitis). Median IFX trough levels just before the first maintenance infusion were significantly higher in children achieving clinical (4.6 μg/mL [2.7–11.8] vs 1.5 μg/mL [0.9–3.0]), biological (4.6 μg/mL [2.5–10.3] vs 2.6 μg/mL [0.3–3.2]) and combined clinical/biological remission (6.0 μg/mL [3.2–12.0] vs 2.6 μg/mL [1.1–3.2]) at week 52 compared to children not meeting these criteria (all P ⩽ 0.002). Binary logistic regression identified these trough levels as the only predictor for the same outcomes with an odds ratio (95% confidence interval) of 2.083 (1.085–3.998), 2.203 (1.101–4.408), and 2.264 (1.096–4.680), respectively (all P  < 0.05). Conclusions: Adequate IFX exposure during induction therapy is associated with better clinical and/or biological remission at week 52. Postinduction IFX trough levels were the only predictor for clinical and/or biological remission at week 52. Abstract : Supplemental Digital Content is available in the text